Effect of molar ratio of KOH to Ti-isopropoxide on the formation of BaTiO3 powders by hydrothermal method - Lee, SK; Choi, G; Hwang, UY; Koo, KK; Park, TJ (ELSEVIER SCIENCE BV, 2003)
Nano-crystalline BaTiO3 powders were prepared using acylated titanium and barium acetate with hydrothermal method. The solution pH given by the molar ratio of KOH to Ti-isopropoxide was found to have an important effect on the size, morphology, and crystallinity of BaTiO3 powders. FT-IR and Raman analyses showed that there were still some Ba-OAc bonds in the structure of as-prepared powders formed from the low pH alkaline solution. As hydrothermal aging time increased, the crystal structure of as-prepared powders was continuously transformed from amorphous to crystalline BaTiO3 powders with breakage of Ba-OAc bonds and elimination of acetyl groups in the powders. When the solution pH was high, most of the acetyl groups bonded to Ba or Ti atoms were eliminated rapidly by hydrolysis in the solution. As a consequence, crystalline BaTiO3 directly precipitated from homogeneous solution via condensation reaction between -Ba-OH and -Ti-OH bonds without subsequent hydrothermal reaction. (C) 2002 Elsevier Science B.V All rights reserved.
Keywords: BARIUM-TITANATE; PARTICLES; PRECURSORS; MECHANISMS